Sarcomatoid Squamous Cell Carcinoma of Vocal Cord: An Uncommon Malignancy - Prasad, Raveena; Bhat, Vadisha; Aroor, Rajeshwary; Hosapatna Laxminarayana, Kishan Prasad (Journal of Health and Allied Sciences NU, 2023)
Sarcomatoid squamous cell carcinoma is a rare variant of laryngeal carcinoma, which comprises 1.3% of all laryngeal malignancies. It is mainly seen in elderly individuals, with smoking and alcohol being common risk factors. The tumor is most common on true vocal cords; hence, patients especially present with dysphonia. We present a case of an elderly male patient who presented with dysphonia due to a vocal cord lesion. During microlaryngoscopy, a firm, exophytic lesion with a narrow stalk was attached to the anterior one-third of the right vocal cord, excised, and sent for histopathology. Histopathology was suggestive of sarcomatoid squamous cell carcinoma. The patient was successfully treated with radiotherapy. We conclude that benign-appearing laryngeal lesions need to be evaluated and histopathological examination to be performed so that rare entities such as sarcomatoid carcinoma, which mimics benign lesions, can be managed appropriately.
Keywords: sarcomatoid; spindle cell; vocal cords; microlaryngoscopy; radiotherapy